Strategic delegation in Nash bargaining - Roland Kirstein (Managerial and Decision Economics, 2023)
Bargainers can increase their outcome by delegation. This paper analyzes delegation contracts consisting of two components: First, a percentage of the outcome if the delegate concludes an agreement. Second, a bonus payment if the delegate fails to do so. This paper derives the effects of these components on the principal's payoff and shows that the optimal contract is unique. Optimally, the principal offers a small share and a high reward for failure to reach an agreement. Delegate's bargaining skills play no role in the optimal contract. The condition is derived under which the optimal contract benefits the principal.
Keywords: 650